PERAN GANDA PEREMPUAN SEBAGAI MAHASISWI DAN IBU MUDA (STUDI KASUS: MAHASISWI PRODI SOSIOLOGI ANGKATAN 2017 FISIP-UNDANA) - Diana Paitei; Susana C. Pellu; Aelsthri Ndandara (Jurnal Pluralis, 2024)
This paper is motivated by the existence of female students who undergo dual roles as students and young mothers. Students who are married and have children must be able to play the role of a wise mother and students who are able to carry out their lecture duties. To be able to carry out this dual role, women need support to be able to minimize inhibiting factors in carrying out the dual role of active students who become young mothers. According to Nature's theory, the distinction between men and women is nature, so it must be accepted. These biological differences provide indications and implications that between the two sexes have different roles and tasks. The method used in this research is descriptive qualitative method, which looks at the uniqueness of human or social symptoms. Qualitative research uses the natural environment as a source of data. The results of this study based on the data obtained show that there are several forms of family support given to female students who undergo dual roles as easy mothers, namely in the form of (1). Providing motivation, (2). Acceptance of children, (3). Supporting financially, (4). Providing facilities. There are also inhibiting factors faced by students who act as young mothers in carrying out their roles, namely (1). restrictions on rights, (2). differences in nature, (3). economic conditions, (4). pressure on self. Conclusions and suggestions from research on women living dual roles based on research cases, namely starting a family at an easy age and not finishing with education, the necessity of starting a family, demands that make it a must. Thus, to undergo a dual role is not easy, it requires maturity in good self-control so that the role can be carried out properly, so that women who live it must be proficient in managing time and finances well so that the family that has been formed is not neglected with other tasks, not only that women who undergo dual roles must be mentally, physically ready for the role they play.